2007
DOI: 10.1158/0008-5472.can-07-1045
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Knockdown Disrupts Glioma Growth In vivo and Displays Synergistic Cytotoxicity with Neural Precursor Cell–Delivered S-TRAIL in Human Gliomas

Abstract: Despite the development of new glioma therapies that allow for tumor-targeted in situ delivery of cytotoxic drugs, tumor resistance to apoptosis remains a key impediment to effective treatment. Mounting evidence indicates that microRNAs (miRNA) might play a fundamental role in tumorigenesis, controlling cell proliferation and apoptosis. In gliomas, microRNA-21 (miR-21) levels have been reported to be elevated and their knockdown is associated with increased apoptotic activity. We hypothesized that suppression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
281
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(291 citation statements)
references
References 35 publications
8
281
1
1
Order By: Relevance
“…Mott et al (2007) described that miR-29b is able to regulate Mcl1-1 protein and thus TRAIL-mediated cytotoxicity in cholangiocarcinoma cell lines. Corsten et al (2007) demonstrated that the combined effect of miR-21 antagonism and soluble TRAIL delivery in glioma cells leads to increase in caspase activity and cell death in glioma cells. More recently, Ovcharenko et al (2007) described a genome-scale miRs and RNAi screen in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mott et al (2007) described that miR-29b is able to regulate Mcl1-1 protein and thus TRAIL-mediated cytotoxicity in cholangiocarcinoma cell lines. Corsten et al (2007) demonstrated that the combined effect of miR-21 antagonism and soluble TRAIL delivery in glioma cells leads to increase in caspase activity and cell death in glioma cells. More recently, Ovcharenko et al (2007) described a genome-scale miRs and RNAi screen in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small fraction of miRNAs have been experimentally examined, among which miR-21 has been well-studied in gliomas. miR-21, which is up-regulated in many solid tumors, inhibits caspase-3 dependent apoptosis in glioma cells and promotes tumor formation in vivo [4]. MiR-21 also facilitates cell invasion by directly targeting metalloprotease inhibitors TIMP3 and RECK [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-21 expression is induced by cytotoxic drugs, such as gemcitabine in cholangiocarcinoma cells, in which the experimental inhibition of miR-21 is able to increase the sensitivity to chemotherapeutic agents (Meng et al, 2006). Remarkably, in a murine model of glioma growth, tumor cell treatment with the anti-miR-21 LNA, exhibiting synergistic cytotoxicity in combination with S-TRAIL, allowed to obtain complete eradication of cancer growth in vivo (Corsten et al, 2007).…”
mentioning
confidence: 99%